2009
DOI: 10.1002/ar.20961
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fiber Population and Biochemical Properties of Whole Body Muscles in Thoroughbred Horses

Abstract: We examine the muscle fiber population and metabolic properties of skeletal muscles from the whole body in Thoroughbred horses. Postmortem samples were taken from 46 sites in six Thoroughbred horses aged between 3 and 6 years. Fiber type population was determined on muscle fibers stained with monoclonal antibody to each myosin heavy chain isoform and metabolic enzyme activities were determined spectrophotometrically. Histochemical analysis demonstrated that most of the muscles had a high percentage of Type IIa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 27 publications
6
45
4
Order By: Relevance
“…longissimus, middle gluteal and biceps femoris (Hyytiäinen et al, 2014;Kawai et al, 2009). The studies confirmed previous research findings demonstrating that the major hindlimb muscles mm.…”
Section: Muscular Control Of Locomotionsupporting
confidence: 90%
See 1 more Smart Citation
“…longissimus, middle gluteal and biceps femoris (Hyytiäinen et al, 2014;Kawai et al, 2009). The studies confirmed previous research findings demonstrating that the major hindlimb muscles mm.…”
Section: Muscular Control Of Locomotionsupporting
confidence: 90%
“…psoas major and sacrocaudalis dorsalis lateralis, had 60-70% fast twitch fibres, while other locomotory muscles, such as mm. iliocostalis and biceps femoris, fell somewhere in between (Hyytiäinen et al, 2014;Kawai et al, 2009). There were some differences between the relative proportions of Type 2A and 2X fibres, with one study using Thoroughbreds following prolonged training and relatively deep samples of muscles (mid-section of muscle) having greater Type 2A than 2X proportions (Kawai et al, 2009 depth had greater proportions of Type 2X than 2A in their locomotory muscles, although this was more pronounced in the Quarterhorses (Hyytiäinen et al, 2014).…”
Section: Muscular Control Of Locomotionmentioning
confidence: 96%
“…For example, the equine gluteus medius, a powerful hindlimb muscle for locomotor propulsion, has been shown to contain a relatively high percentage of fast MHC-2X fibers in addition to MHC-2A and MHC-1 fibers (36,42). Other, more specialized muscles of the distal hindlimb or forelimb, however, do not show concurrent expression of all three isoform fiber types [soleus (21,27) and interosseus (43)] and may be expected to have a primary composition of MHC-1 and MHC-2A fibers, as evidenced in the forelimb digital flexor muscles of horses in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The IIb MHC has the fastest ATPase activity of all MHC isoforms (4). The scaling of body size to muscle speed of contraction is illustrated by the fact that IIb MHC is abundantly expressed in small mammals such as rats, mouses, guinea pigs, and rabbits (15,59), whereas it is not expressed at all in skeletal muscles of most large mammals, such as humans, baboons, horses, cows, goats, dogs, and cats (3,26,31,33,49,50,55).…”
Section: Discussionmentioning
confidence: 99%